LABORATORY STUDIES OF SEISMIC WAVE PROPAGATION IN INHOMOGENEOUS MEDIA USING A LASER DOPPLER VIBROMETER - Nishizawa O.; Satoh T.; Kuwahara Y.; Lei X. (My University, 1997)
We performed physical model experiments by utilizing a laser doppler vibrometer (LDV). Because LDV converts velocity of vibration to the Doppler shift frequency, it enables very precise measurements of ultrasonic waves without any resonating element that conventional transducers usually include. A piezoelectric transducer (PZT) was used as a source of elastic waves, and the waveform was measured in a very small area of about 400 μm in diameter by focusing the beam. We can easily perform very precise measurements of wave field in a physical model, and thus physical model experiments of wave propagation can simulate realistic seismic field observations. For models of inhomogeneous material, we used three granitic rocks with different grain sizes: Westerly granite (fine grained), Oshima granite (medium grained), and Inada granite (coarse grained). Large rock prisms, 300 × 300 × 80 to 90 mm, were used to prevent contamination by multiple reflections from the side ends in the earlier portion of waveforms. The direct P and S waves and reflected waves were identified by their travel times. Observations were made by long in-line, circular, and small-aperture arrays. When the rock grain size becomes comparable to the wavelength, transmitted waves are strongly attenuated by backward scattering, and a large amount of wave energy is transferred to the coda portion. Semblance plots in the time-slowness plane obtained from the small-aperture array suggest that incoherent waves become dominant as the grain size becomes large and comparable to the wavelength.